2008
DOI: 10.1016/j.freeradbiomed.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the site of spin trapping in proteins by a combination of liquid chromatography, ELISA, and off-line tandem mass spectrometry

Abstract: An off-line mass spectrometry method that combines immuno-spin trapping and chromatographic procedures has been developed for selective detection of the nitrone spin trap 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) covalently attached to proteins, an attachment which occurs only subsequent to DMPO trapping of free radicals. In this technique, the protein-DMPO nitrone adducts are digested to peptides with proteolytic agents, peptides from the enzymatic digest are separated by HPLC, and enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
(63 reference statements)
2
34
0
Order By: Relevance
“…The increase in DMPO-protein and -DNA nitrone adducts after I/R injury confirms the protein and DNA radical-scavenging activity of DMPO as previously reported [44][45][46]. The observed decrease in lipid peroxidation after DMPO administration is also in agreement with previous reports showing that DMPO can scavenge lipid radicals [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…The increase in DMPO-protein and -DNA nitrone adducts after I/R injury confirms the protein and DNA radical-scavenging activity of DMPO as previously reported [44][45][46]. The observed decrease in lipid peroxidation after DMPO administration is also in agreement with previous reports showing that DMPO can scavenge lipid radicals [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…61 In Figure 6, it is observed that ethanol presence in the DE formulation did not diminish the ability of BSA to be "recognized" by the antibody, showing that the BSA-antibody complex formation was comparable for all aqueous samples collected from oil-thawed DEs. This result is not surprising because ethanol is not expected to cause strong denaturation of protein, given that the overall ethanol concentration in the aqueous phase was low.…”
Section: Measurement Of Antigen-antibody Interactions By Elisamentioning
confidence: 89%
“…Since the production of the anti-DMPO antibody [23], a number of protein radicals have been detected by DMPO-based IST [21, 32], including myoglobin [23, 3436], hemoglobin [22, 35, 3738], cytochrome c [39], neuroglobin [40], Cu, Zn-superoxide dismutase (SOD1) [4143] and Mn-SOD [44], catalase [33], myeloperoxidase [4546], eosinophil peroxidase [47], lactoperoxidase [4849], microglobulin [50], albumin [43, 51], thyroid peroxidase (TPO)[25], α-lactalbumin [52] and Ras GTPase [53]. Oxidants used to generate these radicals included H 2 O 2 , peroxynitrite, Cu 2+ /H 2 O 2 , hypochlorous acid, tert -butylhydroperoxide, peroxymonocarbonate, and reactive species generated from ketoprofen plus UV-A, riboflavin plus UV-A irradiation and nano-TiO 2 plus UV-A irradiation.…”
Section: Ist Study Of Protein Radicals In Purified Proteinsmentioning
confidence: 99%
“…The site of DMPO trapping on hoMb was determined to be Tyr 103 by MS/MS and site-specific mutagenicity experiments [34, 55]. The LC-ELISA-MS-based strategy [36] is a powerful approach to identifying the sites of DMPO reaction with specific radicalized amino acid residues in the model hemoproteins sperm whale Mb, horse heart Mb and human oxyHb. Importantly, this study by Lardinois et [36] showed that peptides containing Tyr-DMPO adducts are better preserved under neutral or basic conditions.…”
Section: Ist Study Of Protein Radicals In Purified Proteinsmentioning
confidence: 99%
See 1 more Smart Citation